Study on the Dose and Exposure Characteristics of the Automatic Optimization Parameter Mode in Mammography - Moon, Young-Ju; Jung, Hong-Ryang; Lim, Woo-Taek (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of study was to provide useful information on the choice of the AOP mode of units that can improve the quality of breast images and reduce exposure dose by analyzing the dose and exposure characteristics of the AOP mode used in the mammography unit of the digital system. Methods/Statistical analysis: The equipment used in the experiment is GE’s Senographe Pristna and Hologic’s Selenia Dimensions. The phantom used Polymethylmethacrylate phantoms and ACR phantom for the evaluation each according to the automatic exposure control of parameters mode for each equipment to evaluate the average dose. Statistical analysis was performed using one-way ANOVA, and post-hoc was performed using the Tukey method. The statistically significant range was set to (p<0.05). Findings: In the dose evaluation, GE’s Senographe Pristna showed that AGD and ESE were lower in the Dose- mode and, while Hologic’s Selenia Dimensions showed that Auto Time mode was lower in AGD and ESE than the Auto Filter mode in dose evaluation. When compared on the whole, both AGD and ESE showed the lowest dose in the Dose-mode, but no statistical difference was found (p>0.05). In the image evaluation, all the scene modes used in the experiment showed different high and low evaluation scores for each item in the evaluation criteria range, but the Dose-mode is believed to provide high-quality images in diagnosing diseases of the breast, as well as mitigating exposure dose since the Dose-mode was the highest in the calcification detection that is considered crucial in mammography. Improvements/Applications: These results showed that AOP modes applied to mammography units in digital systems can improve the quality of breast images and reduce exposure dose. It is also posited that the results of this study will be used as a baseline data for establishing optimized guidelines for image quality improvement and dose reduction in future mammography examinations.